2020
DOI: 10.1177/0972753120968751
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Idiopathic Generalized Epilepsy on Executive Functions

Abstract: Background: Idiopathic generalized epilepsy is defined as seizures with a possible hereditary predisposition without an underlying cause or structural pathology. Assessment of executive dysfunction in idiopathic generalized epilepsies based on standard Indian battery is not available in the literature. Aims and Objectives: To assess specific executive functions affected in patients with idiopathic epilepsy and their association with various variables. Materials and Methods: Type of observational cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Koganti and his colleagues found problems in planning (Tower of London), verbal fluency (verbal n-back, category fluency, and word fluency), and inhibition (Stroop test) in 75 idiopathic generalized epilepsy adults [23].…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…Koganti and his colleagues found problems in planning (Tower of London), verbal fluency (verbal n-back, category fluency, and word fluency), and inhibition (Stroop test) in 75 idiopathic generalized epilepsy adults [23].…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…Research has shown a notable decrease in higher cognitive functions in patients with pediatric epilepsy compared to individuals without this condition. Deficiencies in various cognitive skills, particularly those involving executive functions, have been identified across multiple studies [6][7][8].…”
Section: Introductionmentioning
confidence: 99%